Incidence and Impact of Non-alcoholic Fatty Liver Disease (NAFLD) in Patients with Adenocarcinoma of the Esophagus Treated with Curative Intent - Lysaght, Joanne; Ravi, Narayanasamy; Reynolds, John; Elliott, Jessie; Conroy, Melissa (My University, 2022)
Background and aims: Esophageal adenocarcinoma (EAC) is associated with visceral obesity (VO). Non-alcoholic fatty liver disease (NAFLD) is common within this phenotype; however, its incidence and clinical significance in EAC have not been studied. Study design: A total of 559 patients with hepatic stetatosis (HS) defined by unenhanced CT were enrolled. In a sub-study, in 140 consecutive patients a liver biopsy was taken intraoperatively to study HS and non-alcoholic steatohepatitis (NASH). Postoperative complications were defined as per the Esophageal Complications Consensus Group (ECCG). Liver biochemistry was measured peri-operatively, with an ALT > 5 defined as acute liver injury (ALI). Mann-Whitney U test or Fisher's exact test was utilized and the Kaplan-Meier method for survival. Results: 42% (n = 234/559) of patients had CT-defined HS. HS was associated with VO in 56% of cases, metabolic syndrome (Met S) in 37% and type 2 diabetes in 25%, compared with 44, 21, and 15% in non-HS patients (p < 0.01). Pathologic HS was present in 32% (45/140) and graded as mild, moderate, and severe in 73, 24, and 3%, respectively, with NASH reported in 16% and indefinite/borderline NASH in 42% of HS cases. Postoperative ALI was similar (p = 0.88) in both HS (10%) and non-HS cohorts (11%). Operative complication severity was similar in both cohorts. 5-yr survival was 53% (HS) vs 50% (p = 0.890). Conclusion: This study establishes for the first time the incidence and clinical impact of NAFLD in EAC patients undergoing surgery and highlights no major impact on oncologic outcomes, nor in the severity of complications.
PUBLISHED
Keywords: Cancer; Immunology, Inflammation & Infection; Cancer/Carcinogenesis; Chronic inflamation; Immune system